Simple Syntheses of Two New Benzo-Fused Macrocycles Incorporating Chalcone Moiety. (29th October 2014) - Mondal, Rina; Samanta, Swati; Sarkar, Saheli; Mallik, Asok K.
Abstract : Simple syntheses of the benzo-fused 26-membered macrocyclic bischalcone (19 E, 43 E )-2.11.27.36-tetroxaheptacyclo[44.4.0.0 4, 9 .0 12, 17 .0 21, 26 .0 29, 34 .0 37, 42 ]pentaconta-1(46), 4(9), 5, 7, 12(17), 13, 15, 19, 21, 23, 25, 29, 31, 33, 37, 39, 41, 43, 47, 49-icosaene-18, 45-dione (3 ) and the benzo-fused 13-membered macrocyclic chalcone (19 E )-2.11-dioxatetracyclo[19.4.0.0 4, 9 .0 12, 17 ]pentacosa-1(25), 4(9), 5, 7, 12(17), 13, 15, 19, 21, 23-decaen-18-one (5 ) using very common starting materials and reagents are described. The compounds are new and they have been characterized from their analytical and spectral data.